Preparation and Absorption Capacities of Two-Component Supramolecular Gels - Huo, Shengwei; Meng, Yuting; Jiao, Tifeng; Ma, Kai; Liu, Yamei; Xing, Ruirui; Zhang, Lexin (Current Nanoscience, 2017)
Background: Two-component gels are a class of gel system which have different functionalized chemical groups and nanoparticles. The aim of this paper is to introduce readers to the new two-component gels system composed of N-(4-aminobenzoyl)-L-glutamic acid diethyl ester with polyacrylic acid by the self-assembly in different solvents. The obtained morphological and spectral data demonstrate that the single or mixed solvents make a great difference on the gelation abilities of these studied supramolecular gels. Methods: All the two-component mixed gels were prepared in an ordinary way. We put the weighted binary mixtures and selected single or mixed solvents measured volume before put these into a sealed glass bottle. Then in order to get a better dispersion we put them all in a sonic bath for 15 min. Later, the solutions were heated at the temperature of 80°C for 20 min in a water bath. Results: Under the SEM technique which can give the typical nanostructures of these gels, the obtained morphologies show many belt-like structures appeared in the xerogels from solvents of benzene and toluene. In addition, the xerogels from ethanol/water mixed solvents with different volume ratios were also characterized by SEM. IR spectra of the obtained gels are demonstrated main peaks, which can be assigned to the carboxyl and N-H stretching, C=O stretching of ester, amide I band, and benzene ring stretching, respectively. Furthermore, the hydrogel exhibits a continuous adsorption process as well as the equilibrium times are approximately 400 min for MB and CR, respectively. It is acceptable that it takes 400 min to reach equilibrium for high-efficiency adsorption illustration. Conclusion: We have achieved the gelation behaviors and adsorption capacities investigation of new two-component supramolecular gels based on glutamic acid diethyl ester derivatives and polyacrylic acid in different solvents. The solvents and molecular skeletons in two-component gelators make a great difference on the gelation abilities of these studied supramolecular gels. Suitable single solvents or proper volume ra> tios of mixed solvents had an obvious influence on regulating the stacking units as well as assembly modes in the present obtained self-assembly gel systems.
Keywords: nanostructure